INTERAKSI KINERJA KEUANGAN PERBANKAN DAN TATA KELOLA DALAM MENINGKATKAN RETURN SAHAM - Ina Marice; Fransiskus E. Daromes; Suwandi Ng (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
This research was conducted to investigate the effect of banking performance on stock returns as moderated by corporate governance. The population used in the study were all banks listed on the IDX for the period 2015-2019. The sample in this study were 30 banks selected using purposive sampling method. The analysis was carried out with the help of SPSS 25 and hypothesis testing using multiple linear regression analysis and moderating regression analysis (MRA). The results of this study indicate that banking performance in the form of LDR, CAR, and ROA partially and simultaneously affects stock returns, NPL partially and simultaneously has no effect on stock returns, governance is able to moderate the relationship between LDR, CAR, and ROA on stock returns, but unable to moderate the relationship between NPL and stock returns.